Solvent-free synthesis of photoluminescent carbon nanoparticles from lignin-derived monomers as feedstock - Márcia G. A. da Cruz; Joy N. Onwumere; Jianhong Chen; Björn Beele; Maksym Yarema; Serhiy Budnyk; Adam Slabon; Bruno V. M. Rodrigues (Green Chemistry Letters and Reviews, 2023)
ABSTRACTPhotoluminescent carbon nanoparticles (CNPs), such as carbon dots (CDs), have attracted much attention owing to a unique set of properties, like high and tunable fluorescence. In this way, the use of carbon-rich lignin has been demonstrated to be a sustainable approach to producing a broad range of photoluminescent CNPs. However, the valorization of this complex polyphenol is limited when it comes to green and efficient ways of conversion. In addition, the existing solvothermal approaches using lignin often result in CDs with low photoluminescence, while flammable and/or toxic solvents are employed. Here, we depolymerized technical lignins, i.e. kraft and soda, through electroreductive cleavage in two different sustainable media: deep eutectic solvent and levulinic acid. After depolymerization, lignin-derived monomers were generated, with a predominance of aryl ether and phenolic groups, which were further combined with 1,2-Phenylenediamine to produce N-doped CNPs in a solvent-free approach. Photoluminescent CNPs with varied sizes were generated (5–50 nm), which presented a wide photoluminescence emission, from blue to red, depending on solvent polarity. These results demonstrate a feasible and sustainable route for the solvent-free synthesis of photoluminescent CNPs using lignin-derived monomers as carbon source, which may find applications in a wide range of fields.